Let's start finding the inverse of the function by changing f(x) to y:
![y=x^2+2](https://img.qammunity.org/2023/formulas/mathematics/high-school/r3ybnebf0uu6qshjtx3i6gfql035wt1wpy.png)
We then interchange x and y, getting:
![x=y^2+2](https://img.qammunity.org/2023/formulas/mathematics/college/4ait4fm32iyevbpav8si0zenuuvztiklug.png)
We now solve for y.
![\begin{gathered} y^2=x-2 \\ y=\sqrt[]{x-2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mz38ltpf8oyu9n5479l4e367w51dttbxgp.png)
Hence, the inverse of the function f(x) = x^2 + 2 is:
![f^(-1)(x)=\pm\sqrt[]{x-2}](https://img.qammunity.org/2023/formulas/mathematics/college/42913au80p4z3obyn6qcxmnuw7hggafdga.png)
Since we are only considering the domain x >= 0, we will only consider the inverse of the function that is positive, that is:
![f^(-1)(x)=\sqrt[]{x-2}](https://img.qammunity.org/2023/formulas/mathematics/college/o0hqomh22dd15xbdudz5yifmcm4ncp3h49.png)
The plot of the function and its inverse is shown in the figure above.